Iterative partial-cancelling MMSE algorithms for W-CDMA MIMO-BLAST systems - Silva, J. C. (2006)
This paper focuses on the usage of an enhanced equalization-based receiver for WCDMA (Wideband Code-Division Multiple Access) MIMO (Multiple Input, Multiple Output) BLAST (Bell Labs Layered Space Time)-type systems. The receiver is based on the MMSE (Minimum Mean Square Error) algorithm coupled with an IPC (Iterative Partial Cancellation) scheme. The scheme is tested in both an uncoded and coded setting, using the UMTS (Universal Mobile Telecommunications System) HSDPA (High Speed Downlink Packet Access) standard as a basis, and the reference UMTS environments.